DEFA after East Germany - Wagner, Brigitta B., 1978- (Screen cultures., 2014)
"In the late 1980s and early 1990s, East Germany's DEFA filmmakers had a brief window in which to critique GDR society on either side of the Wende, the sweeping political turn that surrounded the fall of the Berlin Wall and the opening of the border. Building on the DEFA Film Library's retrospective Wende Flicks series and Indiana University's DEFA Project, this study examines the newly rediscovered filmic artifacts of this transitional cinema, introducing eighteen key films from 1988 to 1994 in essays by German scholars, film professionals, and cultural figures. Accompanying interviews and historical film reviews present a complex portrait of East German film art, its communist bloc influences, and its legacy for contemporary German film culture. The resulting anthology combines historical, autobiographical, cultural-political, and journalistic discourses to explore the tension between the hopes and frustrations these films express, the historical exigencies that overshadowed their production and reception, and the politics of their revival."--